Odpowiedzi

2009-11-26T18:53:43+01:00
X² - 2*x*1 + 1² + x² - 3² = 2x - 2y +2x-4 + 2xy
x² - 2x + 1 + x² - 9 = 4x - 2y + 2xy
2x² - 2x + 8 = 4x - 2y + 2xy
2x² - 2x - 8 = 4x - 2(3x-2) + 2x(3x-2)
2x² - 2x - 8 = 4x - 6x + 4 + 6x² - 4x
2x² - 2x - 8 = -6x + 4 +6x²
2009-11-26T18:55:10+01:00
(x-1)²+(x-3)(x+3)=2(x-y)(x-2)+2xy
y=3x-2

x²-2x+1 + x²-9=2(x²-2x-xy+2y)+2xy
y=3x-2

2x²-2x-8=2x²-4x-2xy+4y+2xy
y=3x-2

2x²-2x-8=2x²-4x+4y |-2x²
y=3x-2

-2x-8=-4x+4y
y=3x-2

2x-4y=8
y=3x-2

2x-4*(3x-2)=8
y=3x-2

2x-12x+8=8
-10x=0

x=0

y=3x-2
y=0-2

y=-2
2009-11-26T19:44:22+01:00
(x-1)²+(x-3)(x+3)=2(x-y)(x-2)+2xy
y=3x-2

x²-x+1+x²-9=2(x²-2x-xy+2y)+2xy
y=3x-2

2x²-x-8=2x²-4x-2xy+4y+2xy
y=3x-2

-x-8=-4x-4y
y=3x-2

3x+4y=8
y=3x-2

3x+4(3x-2)=8
3x+12x-8=8
15x=16
x=16/15
y=4/5